2010
DOI: 10.15288/jsad.2010.71.278
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Levels in the Brain Reward Pathway Discriminate Those Who Remain Abstinent From Those Who Resume Hazardous Alcohol Consumption After Treatment for Alcohol Dependence

Abstract: ABSTRACT. Objective:This study compared baseline metabolite levels in components of the brain reward system among individuals who remained abstinent and those who resumed hazardous alcohol consumption after treatment for alcohol dependence. Method: Fiftyone treatment-seeking alcohol-dependent individuals (abstinent for approximately 7 days [SD = 3]) and 26 light-drinking nonsmoking controls completed 1.5-T proton magnetic resonance spectroscopic imaging, yielding regional concentrations of N-acetylaspartate, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 85 publications
3
40
1
Order By: Relevance
“…Our finding that cluster DTI values differed between the RHU group and control subjects but not between treatment sustainers and control subjects, despite similar lifetime and recent drinking histories, corresponds with other findings of normal baseline brain measures in AUD patients who go on to maintain abstinence (31,32). Thus, as most alcohol use variables in the current study do not appear to be related to the white matter measures, it is possible that factors beyond alcohol use may contribute to the observed white matter integrity difference between AUD groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our finding that cluster DTI values differed between the RHU group and control subjects but not between treatment sustainers and control subjects, despite similar lifetime and recent drinking histories, corresponds with other findings of normal baseline brain measures in AUD patients who go on to maintain abstinence (31,32). Thus, as most alcohol use variables in the current study do not appear to be related to the white matter measures, it is possible that factors beyond alcohol use may contribute to the observed white matter integrity difference between AUD groups.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, reduced baseline frontal cerebral blood flow (11) and abnormal electroencephalogram signals from the frontal lobes (28,29) have been associated with relapse. In addition, lower baseline metabolite levels have been reported in the frontal and temporal lobe regions involved in reward circuitry in treatment-seeking persons with AUD (30,31). Brain volumetric measures of the amygdala and frontal cortex have also been shown to be predictive of relapse and craving (3235).…”
mentioning
confidence: 99%
“…Taken together, these volumetric and perfusion results suggest that Relapsers entered treatment with greater neurobiological abnormalities in their frontal GM than Abstainers, and their deficits were persistent across the 4 weeks while in treatment for AUD. Cross-sectional studies have observed morphological, biochemical and functional connectivity differences between Abstainers and Relapsers in multiple subregions of the frontal lobe (e.g., anterior cingulate cortex, dorsolateral and ventromedial prefrontal cortex, orbitofrontal cortex) implicated in the development and maintenance of AUD (Beck et al, 2012; Cardenas et al, 2011; Durazzo et al, 2010b; Durazzo et al, 2011; Rando et al, 2011). Therefore, assessment of longitudinal changes in these behaviorally relevant frontal subregions is necessary to determine if the Relapsers also continue to exhibit greater abnormalities in functionally important frontal subregions while engaged in the early phase of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lower concentrations of frontal white matter NAA, temporal gray matter NAA, or frontal gray matter Cho were associated with a greater probability of resumption of drinking behavior [55]. A subsequent study from this group showed that those who resumed drinking had decreased levels of NAA in all regions examined than did light drinkers [56]. …”
Section: Metabolic Abnormalitiesmentioning
confidence: 99%